EVALUATION RESEARCH ON DENGUE HEMORRHAGIC FEVER CONTROL PROGRAM - MUENSAN, JUMNONG; SRITHA, SOONTORN; KHEMNARK, NIPON (Maharat Nakhon Ratchasima Hospital Journal, 2025)
Dengue hemorrhagic fever (DHF) is one of the most important public health problem in Thailand last than 40 years. Vulnerable people are children under 15 years both in school and preschool age groups. Nowadays death from DHF is less common but when occur it is severe. Control program by Ministry of Public Health have emphasized on mosquito vector control in both villages and communities. Joint venture between Ministry of Pubic Health and Ministry of Education for DHF control in primary school had launched since 1994. Evaluation research on DHF Control Program Nakhon Nayok has three main objectives: to evaluate input factors, process of operation and output of theprogram. This will lead to the clear understanding of problems and obstacles and may give rise to appropriate solutions. The output of program was studied by epidemiological analysis of case reports in last 5 years and the result shows no definite decreasing trend of DHF incidence. The problems of program management were Planning monitoring, delayed activities, poor co-ordination and poor evaluation especially in pracThere should be the improvement of program management in all levels especially in monitoring, co-ordination and evaluation. There should be the improvement of program management in all levels especially in monitoring, co-ordination and evaluation.